The Effect of Preoxygenation on the Incidence of Desaturation During Induction of General Anesthesia - Tanggono, Aninda (Riwayat: Educational Journal of History and Humanities, 2025)
Desaturation during induction of general anesthesia is a significant clinical concern, leading to complications such as hypoxia and impaired organ function. Preoxygenation is a common practice aimed at increasing the oxygen reserves in the body, thereby reducing the risk of desaturation. However, the effectiveness of preoxygenation in minimizing desaturation during anesthesia induction remains a topic of debate. This study aims to investigate the effect of preoxygenation on the incidence of desaturation during the induction of general anesthesia. To determine whether preoxygenation reduces the incidence of desaturation during the induction of general anesthesia and to identify factors influencing its effectiveness. This prospective cohort study was conducted with a sample of 150 patients undergoing elective surgeries requiring general anesthesia. Participants were randomly assigned to two groups: the preoxygenation group, where patients received 3-5 minutes of preoxygenation with 100% oxygen via a face mask, and the control group, where patients did not undergo preoxygenation. Desaturation, defined as a drop in oxygen saturation (SpO2) below 90%, was monitored continuously during the induction phase. Data were analyzed using statistical tests to compare the incidence of desaturation between the two groups. The preoxygenation group demonstrated a significantly lower incidence of desaturation compared to the control group. The incidence of desaturation was 10% in the preoxygenation group, compared to 25% in the control group (p0.05). Furthermore, preoxygenation was particularly effective in patients with higher body mass index (BMI) and those undergoing longer surgical procedures. Preoxygenation significantly reduces the incidence of desaturation during the induction of general anesthesia, suggesting it is a valuable practice in improving patient safety. The findings support the use of preoxygenation, particularly in patients with higher BMI or those undergoing prolonged surgeries. Future studies should explore the optimal duration and method of preoxygenation to further enhance its effectiveness.